REVIEWS (New blackfriars, 1971)
Book Review in this article THE DEATH OF THE FAMILY, by David Cooper. EVERYDAY LIFE IN THE MODERN WORLD, by Henri Lefebvr FAITH AND PHILOSOPHICAL ENQUIRY, by D.Z. Philips. VOCATION AND FORMATION and CONSERCRATION AND VOWS, by E.F. O'Doherty. THE DEACON IN THE CHURCH: PAST AND FUTURE, by Edward P. Echin BREAKTHROUGH, by Mark School, O.P. THE RELIGIOUS EXPERIENCE OF MANKIND, by Ninian Smart ST THOMAS AQUINAS: SUMMA THEOLOGIAE. VOL. XI: Man (la lxxv-lxxxiii), by Timothy Suttor.